Arsenic intake and dietary risk assessment of coriander (Coriandrum sativum L.) leaves in the Gangetic basin of West Bengal - S Pal, R Kundu, K Bhattacharyya, (Journal of Spices and Aromatic Crops, 2012)
Field experiments were conducted at farmers’ field in Nadia district of West Bengal during winter seasons of 2008–09 and 2009–10 to evaluate the varietal tolerance and arsenic (As) accumulation of different coriander cultivars and As intake and dietary risk assessment of leaves. Results revealed that As accumulation in different plant parts was in the order, root > leaf > stem. Ingestion of significant proportion of inorganic As through consumption of coriander was observed which posed a risk of 36.0% of Provisional Tolerable Weekly Intake.